Facilitating knowledge sharing: A step-by-step process - Gichuki, Leah; Lukuyu, Ben A.; Kiptoo, Emmaculate; Maiyo, Nathan (International Livestock Research Institute, 2024)
Climate change adaptation is a pressing global challenge that requires effective knowledge sharing at local levels. In this manual, we will explore how the Pioneer Positive Deviance (P-PD) team has been facilitating demand-driven training sessions aimed at enabling farmers to adapt their practices to the challenges posed by climate change. Through these training sessions, diverse knowledge systems come together to co-create relevant solutions tailored to local contexts. Here’s a detailed look at the steps involved in this process, illustrating our approach and the unique knowledge shared along the way.